2019
DOI: 10.1016/j.athoracsur.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrate in Cardiac Surgery: A Systematic Review and Meta-Analysis

Abstract: Background. Prothrombin complex concentrate (PCC) has recently emerged as effective alternative to fresh frozen plasma (FFP) in treating excessive perioperative bleeding. We performed a systematic review and meta-analysis to evaluate the safety and efficacy of PCC administration as first-line treatment for coagulopathy following adult cardiac surgery. Methods. We searched PubMed/MEDLINE, EMBASE, and the Cochrane Library from inception to the end of March 2018 to identify eligible articles. Adult patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 44 publications
1
67
3
Order By: Relevance
“…Both plasma and PCCs are effective at restoring thrombin generation in cardiac surgical patients; 129 however, PCCs offer faster, more effective restoration of thrombin generation with reduced volumes and alloantigen exposure 129,130 . A recent systematic review and meta‐analysis of the observational literature comparing 423 patients who received PCCs to 438 who received plasma concluded that PCCs may be associated with a significant reduction in the risk of transfusion and a reduction in the number of units of red cells transfused overall 129 . There was no observed difference between groups in terms of reoperation for bleeding, chest drain output at 24 hours, in‐hospital mortality, stroke, or acute kidney injury.…”
Section: Special Considerations In Refractory Bleedingmentioning
confidence: 99%
“…Both plasma and PCCs are effective at restoring thrombin generation in cardiac surgical patients; 129 however, PCCs offer faster, more effective restoration of thrombin generation with reduced volumes and alloantigen exposure 129,130 . A recent systematic review and meta‐analysis of the observational literature comparing 423 patients who received PCCs to 438 who received plasma concluded that PCCs may be associated with a significant reduction in the risk of transfusion and a reduction in the number of units of red cells transfused overall 129 . There was no observed difference between groups in terms of reoperation for bleeding, chest drain output at 24 hours, in‐hospital mortality, stroke, or acute kidney injury.…”
Section: Special Considerations In Refractory Bleedingmentioning
confidence: 99%
“…55 A more recent meta-analysis, however, did not show any increased risk of stroke with PCC, although the included studies were limited by sample size. 56 Taken together, the hemostatic efficacy of these procoagulants should be weighed against potential thrombotic risks individually.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac surgical procedures at high risk for bleeding after separation from CPB such as those involving the aorta with long CPB and aortic cross-clamp times, refractory bleeding diathesis is commonly managed with the initiation of rescue therapy with recombinant activated factor VII. The evidence for prothrombin complex concentrate products, albeit limited, suggests decreased intraoperative transfusion requirements [8,9]. However, there are also substantial risks which include stroke or other thrombotic events which may be life threatening [10].…”
Section: Introductionmentioning
confidence: 99%